A molecular electron density theory study of the [3 + 2] cycloaddition reaction of nitrones with strained allenes. Issue 43 (17th May 2017) - Domingo, Luis R.; Ríos-Gutiérrez, Mar; Pérez, Patricia
Abstract : The molecular electron density theory study of this [3 + 2] cycloaddition reveals that the strain present in the cyclic allene changes its reactivity to that characteristic of highly reactive radical species. Abstract : The [3 + 2] cycloaddition (32CA) reaction of C -phenyl- N-tert -butylnitrone with 1, 2-cyclohexadiene (CHDE), a strained allene, has been studied within Molecular Electron Density Theory (MEDT) at the DFT B3LYP/6-311G(d, p) computational level. This non-polar 32CA reaction, which takes place through a non-concerted two-stage one-step mechanism, proceeds with a moderate Gibbs free activation energy of 22.7 kcal mol −1, and presents low stereo- and regioselectivities. The reaction begins by the creation of a pseudoradical center at the central carbon of the strained allene with a relatively low energy cost, which immediately promotes the formation the first C–C single bond. This scenario is completely different from that of the 32CA reaction involving the simplest allene. The strain present in CHDE changes its reactivity to that characteristic of radical species. Consequently, not distortion as previously proposed, but the radical reactivity type of the strained allene is responsible for the feasibility of this 32CA reaction.